Early-strength quick-setting lightweight concrete material as well as preparation method and application thereof
By using the synergistic effect of high calcium minerals and aluminate cement and carboxylate-containing retarder in lightweight concrete materials, the problem of insufficient strength in the early stage was solved, and lightweight concrete materials with early strength and rapid concentration and high flow were achieved, improving construction efficiency and compressive resistance.
Patent Information
- Application Number
- CN202311180079.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-14
AI Technical Summary
The existing lightweight concrete materials have shortcomings in early strength, especially in early strength of 2 hours, and are difficult to meet construction needs.
Through the synergistic effect of high calcium minerals and aluminate cement in the formulation system, combined with carboxylate-containing organic acid retarder, adjust the settling time and improve early strength, especially the early strength of 2 hours.
The high flow degree and good 2h compressive strength of early-strength fast-condensing lightweight concrete materials are achieved, which improves construction efficiency and has good construction properties and compressive properties.
Smart Images

Figure BDA0004446927710000101 
Figure BDA0004446927710000111 
Figure BDA0004446927710000112
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete materials, and in particular to an early-strength, fast-setting lightweight concrete material and a preparation method and application thereof. Background Art
[0002] Chinese patent application CN 105523740 A discloses a thermal insulation lightweight concrete material and a preparation method thereof, which is made of the following ingredients: 350-370 parts of composite silicate cement, 70-74 parts of fly ash, 200-224 parts of water, 207.0-250.7 parts of ceramsite, 307.3-361.1 parts of ceramic sand, and 131.7-154.7 parts of sand. This material has high compressive strength, low dry apparent density, good thermal insulation performance, and strong water resistance. This material has the characteristics of thermal insulation, heat insulation, light weight, earthquake resistance, and water resistance.
[0003] Chinese patent application CN 115784690 A discloses a high-temperature resistant EPS concrete material for improving the anisotropy of 3D printing and a preparation method thereof. The concrete material is obtained by uniformly mixing a cementitious material, water, a thickener, a water reducer, an expansion agent, a polystyrene foam aggregate and mixed micro-nano inorganic fibers. The cementitious material is a cementitious system compounded by weight of 100 parts of ordinary Portland cement, 30 to 40 parts of rapid-hardening cement, 25 to 30 parts of fly ash and 6 to 8 parts of silica fume.
[0004] The above-mentioned lightweight concrete materials do not focus on how to improve early strength, especially 2h early strength. Summary of the invention
[0005] The present invention provides an early-strength, fast-setting lightweight concrete material, a preparation method and application thereof. Based on the formulation system of the present invention, an early-strength, fast-setting lightweight concrete material with good early strength, especially 2h strength, can be provided.
[0006] To achieve the purpose, the present invention provides the following technical solutions:
[0007] In one aspect, the present invention provides an early-strength, fast-setting lightweight concrete material, which is prepared by using raw materials including the following components in parts by mass:
[0008] Aluminate cement 10-75 parts, high calcium mineral 15-80 parts, retarder 0.01-2 parts, water reducer 0.001-2 parts, thickener 0.01-0.5 parts, rubber powder 0.01-1 parts, polystyrene foam aggregate 0.1-5 parts;
[0009] Wherein, the free calcium oxide content in the high-calcium mineral is 2-40wt%, preferably 5-20wt%;
[0010] The mass ratio of the aluminate cement to the high calcium mineral is 5:1-40;
[0011] The retarder is an organic acid containing a carboxylate group.
[0012] In the formulation system of the present invention, the components cooperate with each other, high-calcium minerals with specific free calcium oxide content and aluminate cement are added, and the ratio of the two is controlled. At the same time, an organic acid retarder containing a carboxylate group is introduced. Through the interaction between the components in the formulation system, the setting time can be adjusted, and the early strength can be improved, especially the 2h early strength can be improved. The formulation system is used in combination with a water reducer, a thickener, a rubber powder and a polystyrene foam aggregate. Through the interaction between the components, the material density can be adjusted, and an early-strength, fast-setting lightweight concrete material can be obtained.
[0013] In the lightweight concrete material formula system of the present invention, high calcium minerals and carboxylate-containing retarders have a certain synergistic effect with aluminate cement. By adding high calcium minerals to aluminate cement and then compounding carboxylate-containing retarders, and controlling the ratio of aluminate cement and high calcium minerals, the setting time can be effectively regulated, and at the same time, the early strength of the lightweight concrete material will not decrease, but will be improved. This is completely different from the effect of adding retarders to cement base in the past. Conventional operations add retarders to cement base to extend the setting time, but the early strength will also be greatly reduced. The formula system of the present invention, based on the above-mentioned ternary component system, simultaneously adds components such as polystyrene foam aggregate, and through the interaction between the components, a lightweight concrete material with early strength and rapid setting can be obtained.
[0014] By adopting the above-mentioned formula system of the present invention, a fast-setting and early-strengthening lightweight concrete material can be obtained by combining and matching the components in the formula system according to a specific dosage ratio.
[0015] In a preferred embodiment, the retarder is tartaric acid.
[0016] In the present invention, high calcium mineral refers to a mineral with a high free calcium oxide content, specifically a high calcium mineral with a free calcium oxide content of 2-40wt%, and the free calcium oxide content is more preferably 5-20wt%. In some embodiments, the high calcium mineral is selected from one or more of tourmaline slag, fly ash, limestone, and gypsum that meet the above-mentioned free calcium oxide content requirements. Preferably, the fly ash is selected from circulating fluidized bed fly ash. It should be noted that not all minerals, such as not all fly ashes, contain free calcium oxide that meets the above-mentioned content requirements. For example, although the fly ash of a general pulverized coal furnace belongs to a high calcium fly ash with a calcium content of more than 5% or even more than 10%, the above-mentioned synergistic effect of the present invention cannot be achieved by using such fly ash; because the calcium oxide in the fly ash of a pulverized coal furnace is mainly inert calcium oxide, and its free calcium oxide content is difficult to reach 2%-40%. The calcium oxide in the circulating fluidized bed fly ash mainly exists as free calcium oxide. The circulating fluidized bed fly ash with a free calcium oxide content of 2-40% can play a synergistic role with aluminate cement and carboxylate-containing retarder. In addition, the inventors of the present application have found that the free calcium oxide content of high-calcium minerals cannot be too high. For example, if it is higher than 40%, it is easy to cause polystyrene foam aggregate agglomeration and concrete stability, causing cracking and other problems.
[0017] In some embodiments, the water reducer is selected from one or more of naphthalene-based water reducers, polycarboxylate water reducers, and lignin-based water reducers, preferably polycarboxylate water reducers.
[0018] In a preferred embodiment, the thickener is selected from hydroxypropyl methylcellulose with a viscosity of ≥50000 mPa·s. The viscosity of hydroxypropyl methylcellulose can be measured by a viscosity tester. In the formulation system of the present invention, hydroxypropyl methylcellulose with a viscosity of ≥50000 mPa·s is used as a thickener, which is combined with other components in the formulation system to facilitate the uniform distribution of polystyrene foam aggregate in the system and prevent problems such as water seepage and stratification of the material.
[0019] In a preferred embodiment, the rubber powder is selected from renewable latex powder, and preferably the rubber powder is 4036N type renewable latex powder, such as German Wacker 4036N rubber powder.
[0020] In a preferred embodiment, the particle size of the polystyrene foam aggregate is ≤5 mm. In the formulation system of the present invention, the polystyrene foam aggregate with the preferred particle size requirement is used to facilitate obtaining a lightweight concrete material with better early strength and rapid setting.
[0021] In some better embodiments, the early-strength, fast-setting lightweight concrete material is prepared by using raw materials including the following components, in parts by mass: 10-50 parts of aluminate cement, 15-50 parts of high-calcium mineral, 0.1-0.5 parts of retarder, 0.1-2 parts of water reducer, 0.1-0.5 parts of thickener, 0.1-1 parts of rubber powder, and 0.1-5 parts of polystyrene foam aggregate; wherein the free calcium oxide content in the high-calcium mineral is 5-20wt%; the mass ratio of the aluminate cement to the high-calcium mineral is 5:2.5-20. The lightweight concrete material prepared by this preferred scheme not only has an initial setting time of less than 60 minutes, but also has a more excellent 2h compressive strength.
[0022] The present invention also provides a method for preparing the above-mentioned early-strength, fast-setting lightweight concrete material, comprising the following steps:
[0023] The raw materials are mixed with water to obtain the early-strength, fast-setting lightweight concrete material; wherein the amount of water is 0.2-0.9 times the total mass of the aluminate cement and the high-calcium mineral, for example, 0.2, 0.3, 0.5, 0.6, 0.8, 0.9 times, etc.
[0024] The early-strength quick-setting lightweight concrete material provided by the invention has a fluidity of 360-430 mm, an initial setting time of ≤60 min, a final setting time of ≤120 min, and a 2h compressive strength of ≥0.1 MPa.
[0025] The present invention also provides an application, in which the early-strength, quick-setting lightweight concrete material described above or the early-strength, quick-setting lightweight concrete material obtained by the preparation method described above is applied to thermal insulation wall materials or concrete 3D printing.
[0026] The technical solution provided by the present invention has the following beneficial effects:
[0027] The formulation system of the present invention can obtain a concrete material with better fluidity, so that the material has better construction performance, and the lightweight aggregate polystyrene foam balls can be well dispersed and uniformly dispersed to avoid agglomeration or floating on the upper layer of the slurry, and the obtained lightweight concrete material has the characteristics of rapid setting and early strength, especially having better 2h early strength, which is conducive to improving construction efficiency. In addition, the concrete material provided by the present invention has a large amount of solid waste, which can effectively reduce material costs and solve the problem of solid waste accumulation; at the same time, the material preparation process is simple, and it has practicality and industrial feasibility. DETAILED DESCRIPTION
[0028] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.
[0029] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.
[0030] The scheme of the present invention will be exemplarily described below with reference to specific embodiments.
[0031] The detection methods involved in the embodiments or comparative examples are described as follows:
[0032] Initial setting time: Tested in accordance with GBT 50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures";
[0033] Final setting time: Tested in accordance with GBT 50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures";
[0034] 2h compressive strength: tested in accordance with GBT 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete";
[0035] Detection method of free calcium oxide in high-calcium minerals: Test in accordance with GB / T 176-2017 "Chemical Analysis Methods for Cement";
[0036] Fluidity: Determined according to the expansion test method specified in GB / T 50448-2015 "Technical Specifications for Application of Cement-based Grouting Materials".
[0037] Dry density: The determination of dry apparent density is carried out in accordance with the "Technical Standard for the Application of Lightweight Aggregate Concrete" (JGJ / T12-2019) using the whole specimen drying method.
[0038] In the following examples, "parts" are by mass unless otherwise specified.
[0039] Example 1
[0040] This embodiment provides an early-strength, fast-setting lightweight concrete material.
[0041] (1) The raw materials used are described as follows:
[0042] High calcium mineral: circulating fluidized bed fly ash, with an average particle size of 18.9 microns, mainly composed of 20.2wt% SiO2, 10.5wt% Al2O3, 43.3wt% CaO (free calcium oxide and inert calcium oxide) and 8.8wt% Fe2O3, of which the free calcium oxide content is 20wt%;
[0043] Cement raw materials: aluminate cement, Zhengzhou Jianai Special Aluminate Co., Ltd.;
[0044] Retarder: tartaric acid, L+, Nanjing Stabo Trading Co., Ltd.;
[0045] Water reducing agent: polycarboxylate water reducing agent 530P, Nanjing Stabow Trading Co., Ltd.;
[0046] Thickener: Hydroxypropyl methylcellulose, viscosity 100000mPa·s, Hebei Haoshuo Chemical Co., Ltd.;
[0047] Rubber powder: German Wacker 4036N type, Jinan Qiansheng Chemical Co., Ltd.;
[0048] EPS (polystyrene) foam aggregate: EPS foam particles, particle size is 3-5mm, Langfang Best Energy Saving Building Materials Co., Ltd.
[0049] (2) Preparation steps of lightweight concrete materials
[0050] Evenly mix 10 parts of aluminate cement and 40 parts of high calcium mineral, add 0.2 parts of retarder, 0.14 parts of water reducer, 0.14 parts of thickener, 0.23 parts of rubber powder, 1 part of EPS foam aggregate, and 30 parts of water, and stir slowly at a speed of 62±5r / min for 15s in a mixer, and then stir quickly at a speed of 125±10r / min for 25s to obtain a lightweight concrete material.
[0051] Example 2
[0052] Refer to Example 1, except that:
[0053] The high calcium mineral used is: circulating fluidized bed fly ash, with an average particle size of 17.6 microns, a total calcium oxide content of 8wt%, and a free calcium oxide content of 5wt%;
[0054] The preparation steps of lightweight concrete materials are as follows:
[0055] According to the amounts of the components listed in Table 1, aluminate cement and high calcium mineral were uniformly mixed, and retarder, water reducer, thickener, rubber powder, EPS foam aggregate and water were added. The mixture was slowly stirred at a speed of 62±5 r / min for 10 s and then quickly stirred at a speed of 125±10 r / min for 20 s in a mixer to obtain a lightweight concrete material.
[0056] Example 3
[0057] Refer to Example 1, except that:
[0058] The high calcium mineral used is: circulating fluidized bed fly ash, with an average particle size of 20 microns, a total calcium oxide content of 17wt%, and a free calcium oxide content of 10wt%;
[0059] The preparation steps of lightweight concrete materials are as follows:
[0060] According to the amounts of the components listed in Table 1, aluminate cement and high calcium mineral were uniformly mixed, and retarder, water reducer, thickener, rubber powder, EPS foam aggregate and water were added. The mixture was slowly stirred at a speed of 62±5 r / min for 20 s and then quickly stirred at a speed of 125±10 r / min for 30 s in a mixer to obtain a lightweight concrete material.
[0061] Example 4
[0062] Refer to Example 1, except that:
[0063] The high calcium minerals used are: tourmaline slag, with an average particle size of 19.2 microns, a total calcium oxide content of 63wt%, and a free calcium oxide content of 40wt%;
[0064] The preparation steps of lightweight concrete materials are as follows:
[0065] According to the amounts of the components listed in Table 1, aluminate cement and high calcium mineral were uniformly mixed, and retarder, water reducer, thickener, rubber powder, EPS foam aggregate and water were added. The mixture was slowly stirred at a speed of 62±5 r / min for 20 s and then quickly stirred at a speed of 125±10 r / min for 30 s in a mixer to obtain a lightweight concrete material.
[0066] Example 5
[0067] Refer to Example 1, except that:
[0068] The high calcium minerals used are: limestone, with an average particle size of 21 microns, a total calcium oxide content of 56wt%, and a free calcium oxide content of 2wt%;
[0069] The preparation steps of lightweight concrete materials are as follows:
[0070] According to the amounts of the components listed in Table 1, aluminate cement and high calcium mineral were uniformly mixed, and retarder, water reducer, thickener, rubber powder, EPS foam aggregate and water were added. The mixture was slowly stirred at a speed of 62±5 r / min for 20 s and then quickly stirred at a speed of 125±10 r / min for 30 s in a mixer to obtain a lightweight concrete material.
[0071] Comparative Example 1
[0072] The method is carried out in accordance with Example 1, except that the formulation composition and dosage are changed, as shown in Table 1.
[0073] Experimental results: The fluidity of the slurry obtained in this comparative example is 480 mm, which is too fluid; compared with Examples 1-5, this comparative example has the phenomenon that the EPS foam aggregate floats on the upper layer, and the foam aggregate is difficult to be evenly distributed.
[0074] Comparative Example 2
[0075] The same process is carried out as in Example 1, except that 8 parts of EPS foam aggregate are added.
[0076] Results: The prepared lightweight concrete had low early strength due to uneven mixing of EPS.
[0077] Comparative Example 3
[0078] The method was carried out with reference to Example 1, except that the high calcium mineral used was fly ash from a pulverized coal furnace, the total calcium oxide content was 13 wt %, and the free calcium oxide content was 1 wt %.
[0079] Comparative Example 4
[0080] The method is carried out with reference to Example 1, except that the free calcium oxide content of the high calcium mineral used is 45 wt%.
[0081] Experimental results: The comparative example uses a high calcium mineral with too high free calcium oxide content. Compared with the examples, the fluidity of the comparative example is 330 mm. Compared with Examples 1-5, in the comparative example, the EPS aggregate is severely agglomerated and cannot be evenly distributed.
[0082] Comparative Example 5
[0083] The method is carried out with reference to Example 1, except that: the amount of aluminate cement is 45 parts, the amount of high calcium mineral is 4.5 parts, and the mass ratio of aluminate cement to high calcium mineral is 5:0.5.
[0084] Comparative Example 6
[0085] The method is carried out with reference to Example 1, except that: the amount of aluminate cement is 5 parts, the amount of high calcium mineral is 45 parts, and the mass ratio of aluminate cement to high calcium mineral is 5:45.
[0086] Comparative Example 7
[0087] The same method is carried out as in Example 1, except that no retarder is added.
[0088] Comparative Example 8
[0089] The same method is carried out as in Example 1, except that tartaric acid is replaced by citric acid.
[0090] Comparative Example 9
[0091] The method was carried out in accordance with Example 1, except that aluminate cement was replaced by silicate cement (Zuanpai P·O42.5R, Yanshan Holding Group Co., Ltd.).
[0092] Comparative Example 10
[0093] The method is carried out with reference to Example 1, except that aluminate cement is replaced by sulphoaluminate cement (425 grade sulphoaluminate cement, Henan Nuoji Building Materials Co., Ltd.).
[0094] Table 1 Recipe
[0095]
[0096]
[0097] Table 2 Experimental results of Examples 1-5, Comparative Examples 2-3 and Comparative Examples 5-10
[0098]
[0099] During the process of Examples 1-5, the fluidity of the obtained slurry was between 360-430 mm, the foam aggregate and each component were well and evenly mixed, and there was no phenomenon of foam aggregate floating on the upper layer of the slurry or agglomeration; and the initial setting time of the obtained material was ≤60 min, the final setting time was ≤120 min, and it had good 2h compressive strength. The materials obtained in the above Examples 1-5 were tested for dry density, and the dry density was 432-789 kg / m 3 It can be used as a lightweight material.
[0100] Compared with Example 1, in Comparative Example 2, the amount of EPS foam aggregate added to the formulation system reached 8 parts, the fluidity was significantly reduced, and the 2h compressive strength was also significantly reduced.
[0101] Compared with Example 1, in Comparative Example 3, the free calcium oxide content in the high-calcium mineral used is less than 2%, and the initial setting time and final setting time of the obtained material are significantly longer, and the obtained material does not have 2h early strength.
[0102] Compared with Example 1, in Comparative Examples 5-6, the dosage of aluminate cement does not meet 10-75 parts, the dosage of high-calcium mineral does not meet 15-80 parts, and the mass ratio of aluminate cement to high-calcium mineral does not meet 5:1-40. The initial setting time and final setting time of the obtained material are significantly longer, and the material does not have a 2h compressive strength.
[0103] Compared with Example 1 and Comparative Example 7, no retarder was added in Comparative Example 7. As a result, the initial setting time of Example 1 was significantly shorter than that of Comparative Example 7, and the cement had better early strength. It can be seen that in the formulation system of the present invention, the role played by introducing the retarder is significantly different from the role played by adding the retarder to the cement base in the prior art.
[0104] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.
Claims
1. An early-strength, fast-setting lightweight concrete material, characterized in that: The raw materials are as follows: Aluminate cement 10-75 parts, high calcium mineral 15-80 parts, retarder 0.01-2 parts, water reducer 0.001-2 parts, thickener 0.01-0.5 parts, rubber powder 0.01-1 parts, polystyrene foam aggregate 0.1-5 parts; Wherein, the free calcium oxide content in the high-calcium mineral is 2-40wt%, preferably 5-20wt%; The mass ratio of the aluminate cement to the high calcium mineral is 5:1-40; The retarder is an organic acid containing a carboxylate group.
2. The early-strength, fast-setting lightweight concrete material according to claim 1, characterized in that: The retarder is tartaric acid.
3. The early-strength, fast-setting lightweight concrete material according to claim 1 or 2, characterized in that: The high calcium mineral is selected from one or more of tourmaline slag, fly ash, limestone and gypsum.
4. The early-strength, fast-setting lightweight concrete material according to claim 3, characterized in that: The fly ash is selected from circulating fluidized bed fly ash.
5. The early-strength, fast-setting lightweight concrete material according to any one of claims 1 to 4, characterized in that: The water reducer is selected from one or more of naphthalene-based water reducers, polycarboxylate-based water reducers, and lignin-based water reducers, preferably polycarboxylate-based water reducers.
6. The early-strength, fast-setting lightweight concrete material according to any one of claims 1 to 4, characterized in that: The thickener is selected from hydroxypropyl methylcellulose with a viscosity of ≥50000 mPa·s.
7. The early-strength, fast-setting lightweight concrete material according to any one of claims 1 to 4, characterized in that: The rubber powder is selected from renewable latex powder, and preferably the rubber powder is 4036N type renewable latex powder; And / or, the particle size of the polystyrene foam aggregate is ≤5 mm.
8. The early-strength, fast-setting lightweight concrete material according to any one of claims 1 to 4, characterized in that: Aluminate cement 10-50 parts, high calcium mineral 15-50 parts, retarder 0.1-0.5 parts, water reducer 0.1-2 parts, thickener 0.1-0.5 parts, rubber powder 0.1-1 parts, polystyrene foam aggregate 0.1-5 parts; Wherein, the free calcium oxide content in the high-calcium mineral is 5-20wt%; The mass ratio of the aluminate cement to the high calcium mineral is 5:2.5-20.
9. The method for preparing the early-strength, fast-setting lightweight concrete material according to any one of claims 1 to 8, characterized in that: The steps include: The raw materials are mixed with water to obtain the early-strength, fast-setting lightweight concrete material; wherein the amount of water used is 0.2-0.9 times the total mass of the aluminate cement and the high-calcium mineral.
10. An application, characterized in that: The early-strength, quick-setting lightweight concrete material described in any one of claims 1 to 8 or the early-strength, quick-setting lightweight concrete material prepared by the preparation method described in claim 9 is used in thermal insulation wall materials or concrete 3D printing.
Citation Information
Patent Citations
Thermal-insulation light concrete material and preparation method thereof
CN105523740A
High-temperature-resistant EPS concrete material for improving 3D printing anisotropy and preparation method thereof
CN115784690A